1993
DOI: 10.1007/bf01446980
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcome in early aneurysm surgery: a 14 years experience

Abstract: In a consecutive series of 1150 patients with cerebral aneurysms diagnosed in our department by angiography or autopsy between the years 1977-1990, 1007 patients underwent definitive operative treatment of their aneurysms mainly by early surgery. More than half (55%) were operated on during the first three days after subarachnoid haemorrhage (SAH), and more than three quarters (77%) during the first week. The surgical mortality at 30 days was 9%; at one-year follow-up 13% had died. The total management mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(30 citation statements)
references
References 26 publications
4
25
1
Order By: Relevance
“…These variables are also comparable to those presented in the international cooperative study 3,4 and in our previous study of 1007 patients, 2 with the exception of the large proportion of excluded middle cerebral artery aneurysms (Table 1), the most common aneurysms in our institution. 38 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These variables are also comparable to those presented in the international cooperative study 3,4 and in our previous study of 1007 patients, 2 with the exception of the large proportion of excluded middle cerebral artery aneurysms (Table 1), the most common aneurysms in our institution. 38 …”
Section: Discussionsupporting
confidence: 89%
“…of outcome also in most surgical [1][2][3][4]35,39 and in many endovascular [13][14][15][16][17][18]40 series.…”
Section: Koivisto Et Al Treatment Of Ruptured Cerebral Aneurysmsmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall both QOL score and modified Rankin scale were influenced by age, showing a decreasing percentage of patients with good and excellent outcomes in the older age groups. The results of several series of patients with ruptured and unruptured intracranial aneurysms, where patient age has been identified in as an independent predictor of long-term clinical outcome were similar Hernesniemi et al 1993;Deruty et al 1995;Yoshimoto and Kwak 1995;Khanna et al 1996). Gender did not contribute significantly, which is also in agreement with previously published data.…”
Section: Basilar Apex Aneurysmssupporting
confidence: 90%
“…In the series of Hernesniemi et al (27), epilepsy was seen in approximately 14% of patients with acute aneurismal SAH who were treated surgically and who were still alive two months after treatment. Keranen et al (45) reported an overall frequency of 14% of late epilepsy in surgically treated patients with supratentorial aneurysms; 2.5% in patients with preoperative Hunt&Hess grade I and 33% in patients with Hunt&Hess grade III-V. Ukkola et al (83) reported a lower frequency of 8% of secondary epilepsy in their series of 183 consecutive patients operated on for ruptured aneurysms.…”
Section: Seizuresmentioning
confidence: 95%